Análise do perfil vocal de sujeitos com Doença de Parkinson pré e pós-terapia imediata com tubos finlandeses. Um estudo de caso. - Silva, Anelise Aparecida da (2018)
Purpose: Analysing the vocal profile of subjects with Parkinson’s desease diagnosis, pre and post immediate Finnish resonance tubes therapy, as a case study.Methods: a case study, performed with two subjects, both of them with Parkinson’s desease diagnosis, ages between 62 and 66 years old. At first, data was collected through the application of a acoustic-perceptual assessment of vocal quality and them, the voice would be analyzed throght a Vox Metria® program, through sustained vowel /a/ phonation. Subsequently, the Finnish resonance tubes therapy was applied to verify the immediate effectiveness of the therapy. For each subjects, the technique was a different mode of application, one with a depth of straw about 2 cm and other about 10 cm.Results: In the technique number 1, there were a reduction at the fundamental frequency and the maximum intensity in both of the subjects, there wasn’t significant increase at the médium intensity, the maximum phonential time values dicreased for subject 1 and it was increase for subject 2. In the technique 2, every results were increased post method application.Conclusion: The Finnish resonance tubes therapy, in this research, was a effective method increasing the maximum vocal intensity and the fundamental frequency at the Parkinson’s desease subjects.